Social Influence and Price Values on the Behavior of Ruang Guru Application Users Mediated by Intention - Prayogi Eka Saputra; Alfatih Sikki Manggabarani; Guntur Syahputra Saragih (Yayasan Ilomata, 2026)
This study investigates the effect of social influence and price value on the behavior of high school students in using the Ruangguru educational application, with behavioral intention as a mediator. The research addresses the gap in understanding the adoption of digital learning platforms among Indonesian students, where usage decisions are often driven by contextual rather than purely psychological factors. A quantitative approach using PLS-SEM was employed, with data collected from 277 respondents through validated questionnaires (Cronbach’s α > 0.7, AVE > 0.5), chosen for its ability to test both direct and indirect relationships simultaneously. Results indicate that price value has a significant positive effect on user behavior (β = 0.421, t = 5.312, p < 0.001, R² = 0.46), while social influence (β = 0.097, p > 0.05) and behavioral intention (β = 0.083, p > 0.05) do not show significant effects. Descriptive analysis also revealed that 72% of students reported high satisfaction, and 68% expressed willingness to recommend the app, although this intention did not translate into actual usage behavior. These findings highlight that affordability and perceived benefits outweigh peer encouragement or intention in driving adoption, reflecting students’ sensitivity to price-value alignment in digital learning. The study implies that educational technology providers should prioritize accessible pricing strategies, though further research is needed to integrate other UTAUT2 constructs for a more comprehensive understanding.